Effect of pH adjustment and ratio of oppositely charged polymers on the mechanistic performance and sustained release of volatile perfume in interpolyelectrolyte complex microcapsules - Lee, Juhyun; Ngo, Hai V.; Jin, Gang; Park, Chulhun; Park, Jun Bom; Tran, Phuong H.L.; Tran, Thao T.D.; Nguyen, Van H.; Lee, Beom Jin (International Journal of Pharmaceutics, 2021)
In this study, volatile perfume was encapsulated in microcapsules (MCs) via interpolyelectrolyte complexes (IPECs) of oppositely charged polymers, with high encapsulation efficiency, to be delivered in a sustained manner. Positively charged chitosan (CTS) and negatively charged Eudragit® S100 (ES100) were used as eco-friendly biopolymers. Limonene (LMN) was selected as the model perfume. First, the solution of LMN in ethyl acetate and poloxamer 407 (POX407) in acidic solution was emulsified using ultrasonication. CTS and ES100 were added in that particular order to form o/w emulsion. LMN-loaded microcapsules (LMN-MCs) were prepared by adjusting the pH and freeze-drying for solidification. The electrostatic interactions of CTS and ES100 to form IPECs were highly dependent on pH, changing in the microscopic images of emulsion droplets and zeta potential. The NH3+ group of CTS and the COO– group of ES100 caused the electrostatic interactions at a specific pH. The formation mechanism of LMN-MCs was successfully validated using instrumental analysis, charge density, and energy dispersive X-ray spectrometer (EDS) mapping. Encapsulation efficiency, loading content, and release rates of LMN-MCs varied according to the ratios of CTS and ES100, demonstrating optimal performance at a 1:1 ratio. The current LMN-MCs could provide a simple manufacturing process with high performance in terms of encapsulation efficiency (>94%), drug loading, yield and sustained release of volatile perfume for 120 h.
Keywords: Capsules; Delayed-Action Preparations; Hydrogen-Ion Concentration; Perfume; Polymers; Electrostatic interaction; Interpolyelectrolyte complexes; Microcapsule; Oppositely charged polymers; pH adjustment; Sustained release; Volatile perfume